Ethnobotany of food plants utilized by Malay Ethnic in Belitung District, Indonesia - TATIK CHIKMAWATI; SULISTIJORINI SULISTIJORINI; NINA RATNA DJUITA; DIMAS PRASAJA; THOBIB HASAN AL YAMINI; MIFTAHUDIN MIFTAHUDIN; YULIAN FAKHRURROZI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Chikmawati T, Sulistijorini, Djuita NR, Prasaja D, Yamini THA, Miftahudin, Fakhrurrozi Y. 2023. Ethnobotany of food plants utilized by Malay Ethnic in Belitung District, Indonesia. Biodiversitas 24: 2977-2987. Many food commodities in Belitung District, Indonesia are imported from the other islands. However, the local government's experience with the COVID-19 pandemic has encouraged the community to increase the diversification of local food products. Comprehensive data on the species used and the utilization is needed to support the effort. The research aimed to study the potential of plant biodiversity as a food source through ethnobotanical studies of the Malay ethnic group in the Belitung District. The study began by determining key and ordinary respondents using purposive and snowball sampling methods. Furthermore, data were collected through open, semi-structured, and structured interviews. The index of cultural significance (ICS) was determined based on quantitative data. The Malay community in the Belitung District utilizes 181 plant species as food, and most species are wild plants (59%). The number of plants used as food varies among sub-districts and is significantly correlated with forest area in each sub-district. The edible plants are divided into seven utilization categories: fruits, cooking spices, vegetables, sources of carbohydrates, beverage ingredients, grains, and staple food. The most used plant organ is the fruit. The plant with the highest ICS value in four sub-districts, i.e., Membalong, Tanjung Pandan, Sijuk, Badau, was coconut (Cocos nucifera); whereas the highest ICS value in the Selat Nasik sub-district was orange konci (Citrus microcarpa). Rice (Oryza sativa) and white pepper (Piper nigrum) also have high ICS values. Rice is an irreplaceable staple food source, while pepper is a commodity with high economic value for the community. The large number of wild plants the community uses indicates that there are many alternative plant species to meet food needs.